Leucine-rich alpha-2-glycoprotein-1 as a Potential biomarker for polycystic ovary syndrome - Mohamed, Noor Jasim; Al-Ani, Ali Waleed (Iraqi Journal of Science, 2026)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting women of reproductive age, characterized by anovulatory, infertility and metabolic disturbances. This study aimed to assess the diagnostic accuracy of Leucine-rich alpha-2-glycoprotein-1 (LRG1) and xanthine oxidase (XO) activity as novel biomarkers for PCOS, as well as to explore the relationship between LRG1 and XO activity across different groups. A total of 150 married women, aged 18-46 years were enrolled and divided into three groups: 50 with PCOS under treatment, 50 PCOS without treatment conditions shared by women with polycystic ovary conditions, and 50 healthy women. Serum samples were analysed to measure LRG1, xanthine oxidase (XO) activity, and various hormonal levels. The results demonstrated significantly elevated LRG1 levels and XO activity in PCOS patients, with a notable reduction in these markers among PCOS patients receiving metformin treatment compared to control. These findings suggest that LRG1 and XO activity may serve as reliable diagnostic biomarkers for PCOS. Additionally, correlations were observed between LRG1 levels, XO activity and hormonal parameters supporting their relevance in PCOS pathophysiology. This study highlights LRG1 and XO as promising diagnostic tools for PCOS management, warranting further investigation into their mechanistic roles and clinical applications